Stabbing Yourself in the Heart: A Case of Autoimmunity Gone Awry - Vigneswaran, Hari (Case Rep Med, 2015)
Within internal medicine, cardiac and neurologic pathology comprises a vast majority of patient complaints. Physicians and advanced-care practitioners must be highly educated and comfortable in the evaluation, diagnosis, and management of these entities. Chest pain accounts for millions of annual visits to the emergency room with pericarditis diagnosed in approximately four percent of patients with nonischemic chest pain. Guillain-Barre Syndrome is autoimmune polyneuropathy that often results in transient paralysis. Simultaneous diagnosis of both entities is a rare but described phenomenon. Here, we present a clinical case of GBS associated pericarditis. A fifty-five-year-old man with history of renal transplant presented with lower extremity weakness and urinary incontinence. Physical exam and diagnostic studies confirmed Guillain-Barre Syndrome. Patient subsequently developed stabbing chest pain with clinical presentation and electrocardiogram consistent with pericarditis. The patient was successfully treated for both diseases. This case highlights that although infrequent, internal medicine care providers must be cognizant of this correlation to ensure timely diagnosis and treatment.